FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH TERHADAP KOMISI PEMILIHAN UMUM DAERAH DALAM PEMILIHAN KEPALA DAERAH BERDASARKAN UNDANG-UNDANG NOMOR 32 TAHUN 2004 - Tresnasanti, Ni Made Ayu; Budi Arsika, I Made (Kertha Negara : Journal Ilmu Hukum; Vol. 01, No. 05, Juli 2013)
This paper shall be entitled as Supervisory Function of Regional Parliamentwithin the Local Election pursuant to Law No. 32 Year 2004. It shall apply normativelegal research method. As characterized within the typology of a democratic country,the existence of general election shall be prerequisite. Local parliament as therepresentative of a region shall execute its supervising role. As its function to beexecuted, the local parliament shall be assigned to conduct supervision and requestreport to Local General Election Commission (hereinafter shall be “KPUD”) towardsthe conduct and procedure of the head of region. Problem raised within the paper shallbe the source of authority delegated to local parliament to supervise KPUD. Conclusiondrawn shall identify the source of authority is derived from Article 66 (3) of Law No. 32Year 2004 indirectly during the supervision.
Keywords: Controlling function, elections